2016
DOI: 10.1152/ajpregu.00066.2015
|View full text |Cite
|
Sign up to set email alerts
|

Orexin signaling is necessary for hypoglycemia-induced prevention of conditioned place preference

Abstract: While the neural control of glucoregulatory responses to insulin-induced hypoglycemia is beginning to be elucidated, brain sites responsible for behavioral responses to hypoglycemia are relatively poorly understood. To help elucidate central control mechanisms associated with hypoglycemia unawareness, we first evaluated the effect of recurrent hypoglycemia on a simple behavioral measure, the robust feeding response to hypoglycemia, in rats. First, food intake was significantly, and similarly, increased above b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 61 publications
(104 reference statements)
0
19
0
Order By: Relevance
“…The following day, they observed that the rats no longer preferred the side associated with the food treat after experiencing hypoglycaemia in that location. This indicated that the rats were “aware” of hypoglycaemia and found it aversive . This effect was blocked by orexin 1 receptor antagonism, indicating that it was mediated by orexin neurones.…”
Section: Lh/pfh Orexin Neuronesmentioning
confidence: 91%
See 2 more Smart Citations
“…The following day, they observed that the rats no longer preferred the side associated with the food treat after experiencing hypoglycaemia in that location. This indicated that the rats were “aware” of hypoglycaemia and found it aversive . This effect was blocked by orexin 1 receptor antagonism, indicating that it was mediated by orexin neurones.…”
Section: Lh/pfh Orexin Neuronesmentioning
confidence: 91%
“…They also contribute to the CRR via projections to the rostral ventrolateral medulla, leading to activation of the sympathetic splanchnic nerve and epinephrine release from the adrenal medulla . An elegant series of studies showed that orexin neurones also play a role in hypoglycaemia awareness . Hypoglycaemia awareness refers to the symptoms of hypoglycaemia (ie, sweating, anxiety) that alert an individual to falling glucose and prompt corrective behavioural responses.…”
Section: Lh/pfh Orexin Neuronesmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, can neuronostatin activate glucagon production and release from alpha cells already compromised by antecedent hypoglycemia? Future studies should examine this potential protective approach of neuronostatin co-infusion following a severe hypoglycemic episode now that animal models of hypoglycemia unawareness have been developed (8, 14). …”
Section: 1 Neuronostatin As a Potential Co-therapy For The Preventimentioning
confidence: 99%
“…It was my good fortune to lure Nicole to my lab for a 3 year stint, leaving behind her husband at Washington State University to finish his veterinary neurology residency. Over this stimulating 3 year period, we had many discussions and amiable arguments that greatly advanced my understanding of this research area and launched me into this field which would provide me with a great deal of fun, intellectual stimulation and an additional source of long-time NIH funding [25, 3539]. …”
Section: Introductionmentioning
confidence: 99%